Child health in Colombia. Issue 11 (7th July 2009) - Nieto, G Arias; Mutis, F Suescun; Mercer, R; Bonati, M; Choonara, I
Abstract : Colombia is a country with major problems, mainly a high degree of inequality and an unacceptably high level of violence (both armed military conflict and crime related). There are unacceptably high variations in health and health provision. Despite these difficulties, there are important steps being taken by both the government and independent organisations to try and improve child health and to achieve the Millennium Development Goals in relation to poverty, hunger and health issues. The participation of different sectors and stakeholders (including government, non-governmental organisations and other organisations of civil society) is essential to overcome Colombian history and to promote a better place for children.